Fire prevention - Diamantes, David (Thomson Delmar Learning, 2007)
This text is updated to reflect the 2006 ICC and Uniform Fire Codes. It features step-by-step explanations and practical examples of the use of model building and fire prevention codes, including detailed information on the legal, economic, and political aspects of the fire inspection process. It is for use as a key component of any professional fire-inspector training program. It also serves as a reference for building and property maintenance inspectors. -Back cover